G4Killer web application: a tool to design G-quadruplex mutations - Brazda, Vaclav; Kolomaznik, Jan; Mergny, Jean-Louis; Stastny, Jiri (Bioinformatics, 2020)
MOTIVATION: G-quadruplexes (G4) are important regulatory non-B DNA structures with therapeutic potential. A tool for rational design of mutations leading to decreased propensity for G4 formation should be useful in studying G4 functions. Although tools exist for G4 prediction, no easily accessible tool for the rational design of G4 mutations has been available. RESULTS: We developed a web-based tool termed G4Killer that is based on the G4Hunter algorithm. This new tool is a platform-independent and user-friendly application to design mutations crippling G4 propensity in a parsimonious way (i.e., keeping the primary sequence as close as possible to the original one). The tool is integrated into our DNA analyzer server and allows for generating mutated DNA sequences having the desired lowered G4Hunter score with minimal mutation steps. AVAILABILITY AND IMPLEMENTATION: The G4Killer web tool can be accessed at: http://bioinformatics.ibp.cz. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: algoritmy; DNA; G-kvadruplexy; mutace; sekvenční analýza DNA; Mutation; Algorithms; G-Quadruplexes; Sequence Analysis, DNA